2021
DOI: 10.1097/scs.0000000000007507
|View full text |Cite
|
Sign up to set email alerts
|

The Radiological Evaluation of the Crista Galli and Its Clinical Implications for Anterior Skull Base Surgery

Abstract: Introduction: Crista galli is extremely important in the endoscopic transcribriform approaches and some extradural approaches. Because of its clinical significance, the morphometric properties of crista galli should be well known. In this study, it was aimed to examine the morphometry and the pneumatization incidence of the crista galli in cone beam computed tomography (CBCT) images. Material and Methods: In this retrospective study, the length and width of the crista galli were measured in CBCT images of 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…On the other hand, Katakami et al [20] reported that cone-beam computed tomography scanning is better to detect an accessory mental foramen. Although it is known that the cone-beam computed tomography images clearly show bony structures, [21,22] we think that small structures such as accessory mental foramen is readily seen on bony specimens. However, the most crucial disadvantage of dry bone studies is the lack of information such as gender, age, and ethnicity.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, Katakami et al [20] reported that cone-beam computed tomography scanning is better to detect an accessory mental foramen. Although it is known that the cone-beam computed tomography images clearly show bony structures, [21,22] we think that small structures such as accessory mental foramen is readily seen on bony specimens. However, the most crucial disadvantage of dry bone studies is the lack of information such as gender, age, and ethnicity.…”
Section: Discussionmentioning
confidence: 80%
“…In another study, Mladina et al [20] declared that the pneumatized CG height was significantly higher in females than in males on CBCT images of 102 skulls. In another retrospective study with CBCT images of 300 subjects, Uçar et al [32] the average width and length dimensions of the CG were reported to be 14.05 ± 2.98 and 3.69 ± 1.53 mm, respectively, in males, and 14.02 ± 2.90 and 3.77 ± 1.43 mm in females. No significant difference was found between the length and width dimensions of CG and sex.…”
Section: Discussionmentioning
confidence: 94%
“…In the literature, the incidence of pneumatization of CG was examined in the vast majority of the previous studies [1,3,5,6,8,10,13,16,19,20,24,25,29,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The foramen cecum comprises two small alae in the frontal bone and crista galli. 10 The first olfactory nerve is the landmark for the posterior limit of Draf III. Therefore, it was already exposed.…”
Section: Clinical Studymentioning
confidence: 99%